KAJIAN PRINSIP ARSITEKTUR BERKELANJUTAN PADA BANGUNAN PERKANTORAN (STUDI KASUS: MENARA BCA JAKARTA) - Hidayatulloh, Syarif; ., Anisa (MEDIA MATRASAIN, 2021)
In recent years, development has become increasingly busy, making negative impacts on the environment and rapid population growth requiring a balanced supply of energy and natural resources. Sustainable Architecture is the solution to the problem. The model of this concept is that humans will try to use as few resources as possible to improve the quality of life of present and future generations so that they can use existing resources on earth for a long time, of course this requires the response and cooperation of all parties so that the concept of development sustainability can go according to plan. The implementation of this research is very important to describe a picture of future plans, because after all humans will always live side by side with nature. Therefore, building by applying these principles in the concept of sustainable development can achieve a balance from environmental, social and economic aspects, of course it can also be balanced with conditions in priority areas such as cities which become a benchmark for total development, especially office buildings.